Building Student Remote-Work Readiness through Digital Learning: Evidence from Philippine Higher Education - Murilla, Johanna Marie I. (International Review of Management and Marketing, 2026)
The research investigates how remote learning affects student preparedness for their upcoming academic studies and professional career development in Philippine higher education institutions. The researchers conducted their study through a quantitative descriptive-correlational method which involved evaluating survey data that 169 students who had experience with remote and blended learning provided. The study examined four areas which included remote learning perceptions and challenges plus opportunities and academic and peer contact and long-term readiness. The results show that students maintain a positive attitude towards remote learning because it provides them with flexible study options and cheaper study expenses and it helps them develop digital skills. The participants indicated that they experienced ongoing problems which included internet connection issues and interruptions from their home environment and diminished chances for direct communication with others. The study established that three variables which included positive remote learning perceptions and learning challenge management abilities and active academic plus peer socializing led to long-term readiness outcomes. The research findings demonstrate that remote learning enhances employability through its development of self-management and adaptability and digital communication abilities but only if educational institutions establish digital support systems that include all students and deliver effective online teaching methods.